Effect of Cobalt Chloride Additive on the Optical Properties of (PEO/PVA) Composites Thin Films - Mohammed, Alaa J. (International Journal of Psychosocial Rehabilitation, 2020)
Transparent films of (PEO/PVA) polymers composites with different cobalt chloride CoCl2 concentrations were prepared using solution cast technique. Measurements of optical absorption were made for all samples at room temperature across the wavelength. (190 – 1100 nm), It was found to increase in absorption spectra with an increase in the CoCl2 concentration in (PEO/PVA) composites, which has been attributed to the increasing in localized states and the optical absorption was also found to be due to direct transitions. And the values of the optical energy differences changed to less energy on cobalt chloride concentration for direct allowed electronic energy transitions as a result it was decreased from 1.72 to 1.68eV. The optical constant (coefficient of absorption (α), coefficient of extinction (k), refractive index (n), dielectric constant of the real and the imaginary part (εr, εi) and conductance optical (σ)) (PEO/PVA) polymers different composites of cobalt chloride concentrations were calculated.